Representation of gender in migrant health studies - a systematic review of the social epidemiological literature - Lisa Wandschneider; Stephanie Batram-Zantvoort; Oliver Razum; Céline Miani (BMC, 2020)
Abstract Background Gender as a social construct contributes to determine who migrates and which migration-related risks and opportunities emerge in all phases of the migration trajectory. Simultaneously, migration influences the individual as well as societal definition and perception of gender roles. An explicit gender perspective in migration-related epidemiological research can contribute to adequately analyse and interpret the health of migrants. This systematic review gives a comprehensive overview on how gender has been conceptualised, operationalised and measured in social epidemiologic studies aiming to assess the influence of gender on health among migrants. Methods We searched PubMed, Embase, CINAHL, the Cochrane Library, EconLit and PsycINFO and conducted backward reference searching. Reviewers independently selected studies, extracted data and conducted the quality assessment. Eligible studies actively aimed to understand, identify or explain the influence of gender on migrants' health, whereby the role of gender can encompass a variety of mechanisms, processes or states of differentiation, discrimination and/or inequality. Results Almost all of the 43 studies were cross-sectional and focussed on health outcomes in the post-migration phase. The most common theme of research was the health of male migrants in the US, and in particular of men who have sex with men (MSM). All studies treated gender as a binary variable (men vs. women), without discussing additional types of gender identities. A minority of studies differentiated clearly between sex and gender. Gender was mostly operationalised through attitudes toward gender roles and gender-based discrimination, experienced at the individual level. Community and societal level gender measures capturing structural gender determinants were underrepresented. Conclusions The intersections of migration and gender suggested synergistic effects on health that only become visible when considering those two social determinants together. Future research needs to embrace a multilevel and non-binary understanding of gender and reflect on the influence of gender in the different phases of the migration journey. Systematic review registration PROSPERO CRD42019124698 .